A Puppet-based Self-Esteem Intervention and Its Effect on Elementary Students’ Knowledge and Social Behaviors in an Afterschool Setting: An Exploratory Study - Greenlee Rigby; Madelyn Huhn (Undergraduate Research Journal for the Human Sciences, 2023)
In the school setting, teaching students how to effectively navigate social interactions with realistic expectations of themselves has demonstrated success in promoting healthy self- esteem and positive social interactions. There has been limited research on self-esteem and social behavior interventions, though, in the out-of-school setting. Student self-esteem knowledge and teacher-observed social behaviors were assessed before and after a month-long, puppet-based, self-esteem curricular intervention held during an afterschool program for a small group of elementary students. Pre-post intervention, student self-esteem and social behavior knowledge scores significantly (p
Keywords: Elementary students; Self-esteem; Social skills; Afterschool; Puppetry